The Effect of Mathematics Anxiety on Students' Learning Achievement: An Ex Post Facto Study - rofifah Qurrotu’ain; Muhammad Rijal Fadli (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Mathematics anxiety can reduce students' ability to understand and solve mathematical problems, thus affecting their overall attitude towards mathematics. Mathematics anxiety, a psychological factor that can affect students' learning achievement in mathematics learning in high school, makes it the most challenging subject in school. This study aimed to identify the effect of mathematics anxiety on students' learning achievement at the high school level and to analyze strategic factors that can help reduce mathematics anxiety for students. This study used a quantitative method with an ex post facto research type with a correlational design. The population was grade X high school students in South Tangerang, with a sample size of 84. The side technique used cluster random sampling. Data collection used an instrument in the form of a mathematics anxiety and learning achievement questionnaire. Data analysis was carried out through partial correlation and multiple correlation with a significance level of 0.05, and the prerequisite test analysis used normality, linearity, and multicollinearity tests. The results showed that mathematics anxiety influenced by self-efficacy factors, classroom climate, and academic support from parents and peers significantly affected students' learning achievement in high school. Schools can facilitate a more conducive learning environment to minimize mathematics anxiety and improve learning outcomes. Implementing a learning program that is psychologically responsive and adaptive to students' needs is expected to improve students' mathematics achievement significantly..